Increased Bile Acid Synthesis and Impaired Bile Acid Transport in Human Obesity - Haeusler, Rebecca A.; Camastra, Stefania; Nannipieri, Monica; Astiarraga, Brenno; Castro-Perez, Jose; Xie, Dan; Wang, Liangsu; Chakravarthy, Manu; Ferrannini, Ele (The journal of clinical endocrinology and metabolism, 2016)
Context:Alterations in bile acid (BA) synthesis and transport have the potential to affect multiple metabolic pathways in the pathophysiology of obesity.Objective:The objective of the study was to investigate the effects of obesity on serum fluctuations of BAs and markers of BA synthesis.Design:We measured BA fluctuations in 11 nonobese and 32 obese subjects and BA transporter expression in liver specimens from 42 individuals and specimens of duodenum, jejunum, ileum, colon, and pancreas from nine individuals.Main Outcome Measures:We analyzed serum BAs and markers of BA synthesis after overnight fasting, during a hyperinsulinemic-euglycemic clamp, or a mixed-meal tolerance test and the association of BA transporter expression with body mass index.Results:BA synthesis markers were 2-fold higher (P < .01) and preferentially 12α-hydroxylated (P < .05) in obese subjects, and both measures were correlated with clamp-derived insulin sensitivity (r = −0.62, P < .0001, and r = −0.39, P = .01, respectively). Insulin infusion acutely reduced serum BAs in nonobese subjects, but this effect was blunted in obese subjects (δBAs −44.2% vs −4.2%, P < .05). The rise in serum BAs postprandially was also relatively blunted in obese subjects (δBAs +402% vs +133%, P < .01). Liver expression of the Na+-taurocholate cotransporting polypeptide and the bile salt export pump were negatively correlated with body mass index (r = −0.37, P = .02, and r = −0.48, P = .001, respectively).Conclusions:Obesity is associated with increased BA synthesis, preferential 12α-hydroxylation, and impaired serum BA fluctuations. The findings reveal new pathophysiological aspects of BA action in obesity that may lend themselves to therapeutic targeting in metabolic disease.